Conservative Treatment of Postinfarction Left Ventricular Free Wall Rupture - Anh Tuan Vo; Thu Trang Nguyen; Thanh Thuy Tran; Dinh Hoang Nguyen (Case Reports in Cardiology)
Left ventricular free wall rupture is a fatal complication of acute myocardial infarction. Emergency surgical repair is usually indicated to treat this condition. However, in very high surgical risk cohort, conservative treatment can also be considered. We report a case of left ventricle pseudoaneurysm that was successfully treated conservatively in a 4-year period.